The Effect of Equitable Distribution of Public Investment in Education Sector on Improving Educational Indicators in Egypt’s Governorates - Gohar, Karim (The Arab Journal of Administration, 2022)
Education has a direct impact on the economic progress of nations, where the individual productivity rate is affected by the quality and quantity of Education acquired. Education availability means the ability of education system to provide equal opportunities to all education age population for enrollment in and completion of education, targeting as a priority the poor areas regardless of gender, economic or social level, or any other difference. Gains have been made in Egypt’s education sector particularly over the last decade in improving literacy rate and increasing educational participation but major deficiencies persist, despite government expenditure on education sector has been increased, Egypt ranked low in human development reports, educational indicators indicated slow progress, so the researcher focused on studying the fairness of public investment expenditure on education at the governorate level and its impact on educational indicators. The study reached many results such as: government expenditure on education sector has been increased particularly on urban areas, which negatively affected educational indicators, this highly inequitable situation requires fundamental changes throughout the education system, on the other hand spatial justice would mean equal access of all citizens to educational facilities, the researcher also linked several variables such as illiteracy rate and unemployment rate, and others. So public budget should be distributed according to a plan that takes into consideration population size and needs.